2016
DOI: 10.1136/annrheumdis-2015-208304
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalised treatment in primary Sjögren's syndrome: baseline parotid histopathology predicts responsiveness to rituximab treatment

Abstract: RTX treatment in pSS leads to a major reduction of lymphocytic infiltration and to fewer B cells, germinal centres and lymphoepithelial lesions in parotid gland parenchyma. A high pretreatment number of CD20+ B cells/mm parotid gland parenchyma predicts better responsiveness of patients with pSS to RTX treatment. Pretreatment parotid gland histopathological characteristics could therefore contribute to a more personalised treatment approach to pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 37 publications
8
64
0
2
Order By: Relevance
“…Using a different definition of clinical response, i.e., a decrease of ≥3 in the ESSDAI, we have shown that both baseline absolute numbers of B cells and the B cell proportion in parotid gland tissue are higher in responders versus non-responders [25,60]. Explanations for the apparent discrepancy between the study of Cornec et al and our study have been extensively discussed elsewhere [60,61].…”
Section: Predictors Of Response To Rituximabmentioning
confidence: 49%
See 2 more Smart Citations
“…Using a different definition of clinical response, i.e., a decrease of ≥3 in the ESSDAI, we have shown that both baseline absolute numbers of B cells and the B cell proportion in parotid gland tissue are higher in responders versus non-responders [25,60]. Explanations for the apparent discrepancy between the study of Cornec et al and our study have been extensively discussed elsewhere [60,61].…”
Section: Predictors Of Response To Rituximabmentioning
confidence: 49%
“…We have found that intra-epithelial FcRL4+ B cells are almost completely depleted by rituximab [29]. Furthermore, rituximab treatment reduces the severity of lymphoepithelial lesions, and concomitantly leads to restoration of the epithelium [25]. It would be of value to study whether rituximab-treated patients develop MALT-lymphoma less frequently than untreated patients.…”
Section: Histological Markers Of B Cell Hyperactivitymentioning
confidence: 92%
See 1 more Smart Citation
“…Serial sections were stained with H&E, and immunohistochemically for B-cell lymphoma six protein (Bcl6, clone GI191E/A8, Ventana, Illkirch, France) and CD45 (clone 2B11+PD7/26, Ventana, Illkirch, France). Staining was performed on a Ventana Benchmark platform as previously described 14. In H&E stained sections, FS, lymphoepithelial lesions (LELs) and GCs were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…We read with great interest the recent contribution by Delli et al ,1 which aimed at determining whether salivary gland histopathology could predict the response to rituximab in patients with primary Sjögren's syndrome (pSS). These authors concluded that a high number at pretreatment of CD20 + B cells/mm 2 of parotid gland parenchyma predicted better responsiveness of patients with pSS to rituximab treatment.…”
mentioning
confidence: 99%